Deteksi Stunting Pada Balita Di Posyandu Mawar Iv Dusun Kalongan Kulon, Papahan, Tasikmadu, Karanganyar - Suwarnisih Suwarnisih; Hastutik Hastutik; Yeni Anggraini (WASATHON Jurnal Pengabdian Masyarakat, 2024)
The problem of stunting is still a national problem in Indonesia, so good efforts are needed to reduce the stunting rate in Indonesia. Stunting is a chronic nutritional problem caused by insufficient nutritional intake in the first 1000 days of life (HPK). Stunted toddlers will have less height compared to their age. Based on the results of the 2021 Indonesian Nutritional Status Study (SSGI), the prevalence of stunting among toddlers in Indonesia according to height-for-age results reached 24.4%. Impaired growth and development is a serious problem for developed and developing countries in the world. Growth can be seen from body weight, height and head circumference, LILA, while development can be seen from motor, social and emotional abilities, language abilities and cognitive abilities. The aim is to detect stunting in children under five according to age stages based on gender with TB so that growth is monitored and children do not experience obstacles. The results of the activities of 63 toddlers were 37 toddlers (58.7%) female, 26 toddlers (41.3%) male, most of the toddlers had nutritional status based on PB/U or TB/U in the normal category, 59 toddlers (93.8%). %) and there are 2 toddlers (3.1%) in the very short category (severely stunted), 2 toddlers (3.1%) in the short category (stunted).